Society and ideology in India : essays in honour of professor R.S. Sharma - Jha, D.N.; Sharma, Ram Sharan, 1920-2011.; Jha, D. N. (Dwijendra Narayan), 1940- (New Delhi : Munshiram Manoharlal Publishers, 1996)
Research papers covering ancient, medieval, and modern periods of Indian history.
Keywords: India -- History; 56-92